Aggregate Planning using Overtime and Adding Number of Employees to Meet the Convection Industry’s Demand - Yuli Eni; Bachtiar H. Simamora (International Journal of Organizational Business Excellence, 2022)
The research aimed to propose the implementation of prediction (forecast) using the approaches of overtime and adding the number of employees in convection industry. This study uses a descriptive type of research with time series method. The research data is quantitative data, which is processed by forecasting methods through Zaitun Time Series, as well as aggregate planning. The data collection techniques are such as interviews, documentation and observations. The results show that the best methods to calculate the prediction in Convection Industry are the Decomposition Multiplicative and Decomposition Additive methods. Conducting aggregate planning in Convection Industry with overtime approach for the Wool Peach product(s) costs about Rp 38,689,840,000; for the Max Mara product(s) it costs about Rp 8,344,647,000; while for the Rayon product(s) it costs about Rp 10,769,950,000. Meanwhile, conducting aggregate planning in Convection Industry with the approach of adding the number of employees for the Wool Peach product(s) costs about Rp 38,630,470,000; for the Max Mara product(s) it costs about Rp 8,343,099,000; while for the Rayon products(s) it costs about Rp 10,768,180,000. Convection Industry is recommended to apply the approach of adding the number of employees so as to increase production rather than using the overtime approach (ARRR, AR).